PENGARUH DISIPLIN KERJA DAN PEMBERIAN INSENTIF TERHADAP KINERJA KARYAWAN PT WISATALOKA - Sugiyah, Sugiyah; Yuliantari, Kartika; Nurhidayati, Nurhidayati (Journal of Information System, Applied, Management, Accounting and Research, 2024)
Human resources (HR) are an important part of a company. This is because HR is an asset for the company, which contributes to the progress of a company. Employees are required to continue to improve their performance, which in turn can significantly improve company performance. The company has made various efforts to encourage employees to continue to improve their performance. Work discipline is one of the factors that can influence employee performance. Disciplinary attitudes arise from employees and also need to be supported by the company, for example with regulations. Another factor that encourages employee performance is the provision of incentives. The company policy provides incentives to encourage employees to work harder. The aim of this research is to examine the influence of work discipline and incentives on employee performance, both partially and simultaneously. The research method used was quantitative with a sample of 50 respondents. Data collection was carried out through observation, questionnaires and documentation. Work discipline (X1) and incentives (X2) are the independent variables and the dependent variable is employee performance (Y). By using the SPSS 26 application for multiple linear regression analysis. The results of this research show that partially, work discipline has a significant effect on employee performance and providing incentives has a significant effect on employee performance. Furthermore, work discipline and providing incentives simultaneously influence employee performance.